Mentoring away the glass ceiling in academia : a cultured critique - Marina, Brenda Louise Hammett (Lexington Books, 2015)
Mentoring Away the Glass Ceiling in Academia: A Cultured Critique describes how women of diverse backgrounds perceive their mentoring experiences or the lack of mentoring experiences in the academy. This book provides a space for envisioning strategies and practices to improve mentoring practices and the collegiate environment.